(untitled) (Materiali di Estetica. Terza serie, 2018)
The essay examines one of the aspects by which the concept of "Interpretation" is expressed, as presented by Paul Ricoeur in his Della interpretazione. Saggio su Freud, that is, writing and its possible different forms. It was read on 21st November 2015 during the Mario Bonfantini Day, in Verbania.